20 Renal recovery following use of left ventricular assist device in advanced heart failure patients. (5th June 2017) - Musa, Tarique; Chue, Colin; Lim, Hoong Sern
Abstract : Background: The National Institute of Health and Care Excellence advocates the use of a Left Ventricular Assist Device (LVAD) as a bridge to transplant, and furthermore as destination therapy in patients who are otherwise ineligible to receive transplantation. Accordingly, the UK has witnessed a sharp increase in the use of LVAD implantation as mechanical circulatory support in patients with advanced heart failure. Heart Failure and kidney disease are significant public health concerns, and given patients with renal dysfunction have largely been excluded from heart failure trials; their optimal management remains unclear. Aim: To assess renal outcomes in patients with advanced heart failure, at both early and mid-term follow-up, following LVAD implantation. Methods: A retrospective single-centre analysis was conducted in 64 consecutive patients implanted with either HeartMate II or HeartMate III continuous-flow LVADs (Thoratec Corp., Pleasanton, California). Renal biochemical profile and estimated glomerular filtration rate (eGFR) was assessed immediately prior to, 30 days and 6 months following LVAD implantation. For the purposes of statistical analysis, stages of chronic kidney disease were defined to reflect the Kidney Disease Outcomes Quality Initiative (Stage 1; GFR 90+, Stage 2; GFR 60–89, Stage 3; GFR 45–59 (KDOQI Stage 3A), Stage 4; 30–44 (KDOQI Stage 3B), Stage 5; GFR 15–29). Patients on dialysis were excluded. Results: 64 patients (age 52.5±11.5 years, 88% male, 14% diabetic, median INTERMACS Profile 3 (IQR 3.00), cardiac output 3.51±0.99 L/min) were studied immediately prior to LVAD implantation, and subsequently at 30 days (n=60) and 6 months (n=42). The results are summarised in Table 1. Significant statistical improvements were seen in urea, creatinine and CKD stage at 30 days; with the improvement in eGFR from baseline persisting at 6 months. In sub-group analysis, excluding patients with normal baseline renal function (defined as CKD Stage 1, n=10), a significant improvement in CKD stage was seen both early (3.0 (IQR 2.0) vs 2.0 (IQR 1.0), p<0.001) and at mid-term (3.0 (IQR 2.0) vs. 2.0 (IQR 1.0) p=0.004). Conclusions: Renal impairment in patients with end-stage heart failure prior to LVAD placement is common and reversible. An early and marked improvement in renal biochemistry from baseline, persisting at 6 months, is seen following LVAD implantation, suggesting poor renal perfusion as a primary aetiology. Given the improvement in CKD stage by an average of 1 grade; further work is required to determine whether LVAD is the treatment of choice in those with significant baseline renal dysfunction.